Does Size Matter? An Analysis of the Effect of Lumbar Disc Herniation Size on the Success of Nonoperative Treatment. Issue 7 (October 2020) - Gupta, Anmol; Upadhyaya, Shivam; Yeung, Caleb M.; Ostergaard, Peter J.; Fogel, Harold A.; Cha, Thomas; Schwab, Joseph; Bono, Chris; Hershman, Stuart
Study Design: Retrospective study. Objective: In this study, we examined whether the size of a lumbar disc herniation (LDH) is predictive of the need for surgical intervention within 2 years after obtaining an initial magnetic resonance imaging (MRI) scan. We hypothesized that a fragment that occupied a larger percentage of the spinal canal would not predict which patients failed conservative management. Methods: Using the ICD-10 code M51.26, we identified patients at a single academic institution, across the 2-year period from 2015 to 2016, who received a diagnosis of primary lumbar radicular pain, had MRI showing a disc herniation, and underwent at least 6 weeks of nonoperative management. Patients experiencing symptoms suggesting cauda equina syndrome and those with progressive motor neurological deficits were excluded from analysis, as were patients exhibiting "hard" disc herniations. Within the axial view of an MRI, the following measurements were made on AGFA-IMPACS for a given disc herniation: the length of both the canal and the herniated disc along the anterior-posterior axis, the average width of the disc within the canal; the total canal area, and the area of the disc herniation. Data analysis was conducted in SPSS and a 2-tailed reliability analysis using Cronbach's alpha as a measure of reliability was obtained. Results: A total of 368 patients met the inclusion and exclusion criteria for this study. Of these, 14 (3.8%) had L3-L4 herniations, 185 had L4-L5 herniations (50.3%), and 169 had L5-S1 herniations (45.9%). Overall, 336 (91.3%) patients did not undergo surgery within 1 year of the LDH diagnosis. Patients who did not receive surgery had an average herniation size that occupied 31.2% of the canal, whereas patients who received surgery had disc herniations that occupied 31.5% of the canal on average. A Cronbach's alpha of .992 was observed overall across interobserver measurements. After controlling for age, race, gender, and location of herniation through a logistic regression, it was found that the size of the herniation and the percentage of the canal that was occupied had no predictive value with regard to failure of conservative management, generating an odds ratio for surgery of 1.00. Conclusions: The percentage of the spinal canal occupied by a herniated disc does not predict which patients will fail nonoperative treatment and require surgery within 2 years after undergoing a lumbar spine MRI scan.